Characterization and profile of graduates from the graduate programs of FMVZ – UNESP – Botucatu (Area of Veterinary Medicine / 2015-2019) - de Lalla Júnior, José Roberto; Hussni, Carlos Alberto (Revista Brasileira de Pós-Graduação, 2025)
The study aimed to characterize and determine the profile of graduates, between 2015 and 2019, of the Graduate Programs, in the area of ​​Veterinary Medicine, of the School of Veterinary Medicine and Animal Science of the São Paulo State University – Unesp, at the Botucatu Campus, comprising the Graduate Programs in Wild Animals, in Animal Biotechnology and in Veterinary Medicine. Specifically, the objective was also to identify the sociodemographic variables and training of these graduates, as well as verify, from the students’ perception, the strengths and weaknesses of the Programs, the main skills acquired throughout the course, analyze the involvement of these students regarding scientific production and participation in technical and scientific events and, finally, to know, in general, the degree of student satisfaction after completing the course. From the application of a semiopen questionnaire in an online format, responses were obtained from 376 graduates, out of the 401 eligible, a fact that corresponds to 93.8% of the target public. The results showed a high degree of satisfaction with the course after completion (90.4% considered it excellent and/or good). Nevertheless, there was a great involvement of students with solid technical training. However, the reports demonstrated the need to develop skills aimed at teaching practice, offering disciplines aimed at teacher training involving pedagogy, statistics/biostatistics, scientific writing, entrepreneurship and academic management. Public-private partnerships should also be encouraged, with a view to developing research and absorbing these professionals into the labor market.